Analysis of Badminton Game Performance: Prediction of Subjective Skill Results and Accuracy of Playing Performance (Universitas Pendidikan Indonesia, 2025)
This study aimed to test and analyze the variability of subjective rating test and accuracy-based test types of badminton skills tests on athlete game performance. The study was conducted using quantitative descriptive methods carried out on 50 badminton school athletes in the West Java PBSI Provincial Government with inclusive criteria for students or beginner athletes. There were three instruments used in the study, including Badminton skill learning outcome test for measuring the movement process (subjective rating test), Badminton skill learning outcome test form measuring the accuracy of the strokes (accuracy-based test), and Badminton performance test. All data generated in this study were analyzed using percentage analysis to determine the success of athletes in carrying out the test and linear regression analysis to test the variability or prediction of subjective rating test and accuracy-based test results on athlete game performance. The results of the analysis showed that 1) the results of the subjective badminton skills test were positively and significantly correlated with the results of the accuracy test and 2) the results of both subjective and accuracy skills tests had a significant effect on athlete performance when playing. It shows that good subjective and accuracy skills are predicted to have an impact on the results of the athlete game performance.